Benzocaine-Induced Methemoglobinemia. A Clinical Case - Rustem F. Tepaev; Vladimir A. Vishnevskiy; Sergey A. Kuzin; Iuliia V. Sergey; Olga B. Gordeeva; Anna V. Pytal; Nikolay N. Murashkin (Union of pediatricians of Russia, 2018)
The article describes a clinical case of the development of a severe, life-threatening methemoglobinemia in a patient with a dystrophic form of congenital epidermolysis bullosa while receiving a drug containing benzocaine. The current data on classification, pathogenesis, clinical course and methods for treating this state has been presented. Many substances and drugs that are methemoglobin formers are widespread and can cause chronic methemoglobinemia. Acute severe methemoglobinemia is accompanied by life-threatening organ disorders. In some cases, it may be difficult to diagnose methemoglobinemia due to the polymorphism of the clinical picture, the need for laboratory confirmation of the diagnosis, which may be underperformed in the absence of adequate alertness. The presented clinical case will be useful for doctors of various specialties.